Aktivitas Antibakteri Fungi Endofit Daun Sirsak (Annona muricata Linn.) terhadap Vibrio cholerae dan Bacillus subtilis - Ratnah, St.; Andriani, Novita; Daswi, Dwi Rachmawaty; Pakadang, Sesilia Rante; Salasa, Alfrida Monica (Jurnal Farmasi Udayana, 2024)
Sirsak plant is traditional plant that believed empirically as cough medicine, dysentery, rheumatism, lowering uric acid levels and diarrhea community. Vibrio cholerae and Bacillus subtilis types bacteria can cause diarrhea. This study aims to determine the number endophytic fungi found from Sirsak leaves, to determine antibacterial activity endophytic fungi isolates from Sirsak leaves against Vibrio cholerae, and Bacillus subtilis. Furthermore, inoculated repeatedly on SDA for 5-7 days until isolates were obtained. Each isolate was fermented with GDP for 2-3 weeks and then extracted with ethyl acetate. Ethyl acetate extract was used antibacterial with agar diffusion method MHA media. Test results showed that 5 isolates were obtained, namely White DS isolate, Toska DS isolate, Green DS isolate, Cream DS isolate, and Blackish Brown DS isolate. Where DS White isolate suspected of Cylindrocladium sp, DS Toska isolate suspected of Aspergillus fumigatus, DS Green, isolate suspected of Aspergillus flavus, DS Cream isolate suspected of Aspergillus terreus, DS Blackish Brown isolate suspected of Aspergillus niger. Sirsak leaf endophytic fungal isolates (White DS, Toska DS, Green DS, Cream DS and Blackish Brown DS) showed antibacterial activity against Vibrio cholerae and Bacillus subtilis.